If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + 5 = 75 + -6t Reorder the terms: 5 + T = 75 + -6t Solving 5 + T = 75 + -6t Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + T = 75 + -5 + -6t Combine like terms: 5 + -5 = 0 0 + T = 75 + -5 + -6t T = 75 + -5 + -6t Combine like terms: 75 + -5 = 70 T = 70 + -6t Simplifying T = 70 + -6t
| y-1/20=13/20 | | 53/4-15/4 | | 4(-8n-3)+4n=-6(5n-3) | | -6(x+3)-15=13+8 | | 8x^3-18x^2-2x+3=0 | | f(x)=x+3 | | 1250x+1000=1450x+1000 | | 3n+3=240 | | 24x^3-9x^2-18x=3x | | F^2+33f=0 | | 4x-9+5x=72 | | x/3-x=4 | | 131/4-33/4 | | 3n+6=126 | | 32x-1=27x | | 9+4x+5x=99 | | (x+x-5x-9)/(x-2) | | -87+y=-18 | | 7/11*2 | | 7h-4(h-3)=18 | | 2/11+5/11 | | 3.4g=5.8 | | 40x+5y=55 | | 3x+(x+10)=180 | | f(x)=-2x+1 | | 2x+5x+10=90 | | -3(2y+7)= | | 4/5-(-1/3)^2 | | 5x+2*3x+4= | | (6-v)(3v-5)=0 | | 2.5w=40 | | 3x=y+4 |